Impact of Exercise Interventions on Elderly Heart Failure: Evaluating Aerobic, Resistance, and Combined Approaches - Ran Lifeng (Ilmu Inovasi Nusantara, 2024)
In recent years, the number of elderly individuals has continued to rise, particularly in China, where aging has become a serious issue. Common symptoms of aging, such as hypertension, heart disease, and osteoporosis, are increasingly prevalent. Heart failure, a complication of heart disease, primarily affects the elderly and can severely impact their quality of life, even posing life-threatening risks. This study explores the impact of exercise interventions on the treatment and rehabilitation of heart failure in the elderly, aiming to provide more comprehensive and effective evidence. Keywords such as